Synthesis and biological evaluation of some novel quinoxaline derivatives as anticonvulsant agents - Elhelby, Abdelghany Aly; Ayyad, Rezk Rezk; Zayed, Mohamed Fathalla (Arzneimittelforschung, 2011)
In view of their expected anticonvulsant activity, some new derivatives of quinon-xaline (V1–7) were designed and synthesized by condensation of different aromatic aldehydes with 2-(2-oxo-3-phenyl-quinoxalin-1 (2H) -yl) acetohydrazide (IV). All synthesized compounds were isolated and confirmed by IR, 1H-NMR, MS, elemental analysis and then tested as anti-convulsant agents. Compound V3 and V1 showed the highest anticonvulsant effect with anticonvulsant potency relative to phenobarbital sodium of 0.8 and 0.75 whereas compound V5 exhibited the lowest relative potency of 0.09. The other compounds showed variable activity between these values as follows: V2 = 0.19, V4 = 0.41, V6 = 0.1 and V7 = 0.15. All compounds showed less activity than the reference compound phenobarbital. But the compounds provided a basis for further optimization.
Keywords: Anticonvulsant drugs; Arylidene; Quinoxaline derivatives; Synthesis